Chemical composition of the essential oil of Hypenia helenoi M.T. Faria - Costa, Devyllen Cristina; de Jesus, Camila Fernandes; Faria, Maria Tereza; Ferreira, Heleno Dias; Ferri, Pedro Henrique (Seven Editora, 2023)
Hypenia has been subject to taxonomic variations, from one botanical section to a genus of Hyptidinae and remaining undivided or divided up into seven infrageneric sections. Essential oils (EOs) constituents of Hypenia were described only recently and supported the division of the genus into two taxonomic sections. In this work, the composition of EOs of H. helenoi was analyzed using gas chromatography coupled with quadrupole mass spectrometry (GC/MS). Hydrodistillation of aerial parts led to 45 compounds, with emphasis on sesquiterpene hydrocarbons (78%) such as b-element (27%), germacrene D (20%), (E)-caryophyllene (7%) and bicyclo germacrene (6%). b-Pinene (4%) was the majority among the monoterpenes (10%), suggesting the mevalonate pathway in EO biosynthesis. Minor constituents such as globular, spathulenol, and humulene epoxide II were rarely identified in the family (Lamiaceae), while other constituents were described for the first time in the genus.DOI: https://doi.org/10.56238/devopinterscie-012